2003
DOI: 10.1021/jp0303321
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Alkoxy Radicals Derived from Isoprene:  Pressure- and Temperature-Dependent Decomposition Rates

Abstract: Pressure-and temperature-dependent thermal decomposition rates for the primary alkoxy radicals derived from OH-initiated oxidation of isoprene have been calculated. The master-equation calculations are based on ab initio energetics and structures previously reported. We also provide analytical descriptions of the theoretical falloff curves using the semiempirical Troe formalism. Additional calculations are also provided for two isomers not previously reported and to further characterize basis set effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 44 publications
1
39
1
Order By: Relevance
“…The reaction of the peroxy radical with NO yields an alkoxy radical which undergoes a δ 5 1 isomerization (Atkinson, 1997;Park et al, 2004). The resulting β-hydroxy allyl radical can then react with O 2 and form a 1,4-hydroxycarbonyl, (2Z)-4-hydroxy-2-methylbut-2-enal (HC5 Z(1,4)) detected as a cluster at m/z=185 (Fig.…”
Section: δ-Hydroxy Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of the peroxy radical with NO yields an alkoxy radical which undergoes a δ 5 1 isomerization (Atkinson, 1997;Park et al, 2004). The resulting β-hydroxy allyl radical can then react with O 2 and form a 1,4-hydroxycarbonyl, (2Z)-4-hydroxy-2-methylbut-2-enal (HC5 Z(1,4)) detected as a cluster at m/z=185 (Fig.…”
Section: δ-Hydroxy Channelsmentioning
confidence: 99%
“…In this study, we assume that channels (2, 1) (respectively (3, 4)) yield MVK and MACR. Park et al (2003) proposed that the radicals formed in these channels undergo a cyclization, thus reducing the yield of MVK and MACR. The yield of the nitrates which should originate from the hydrocarbons proposed by Park et al (2003) is too small to provide conclusive experimental evidence in favor or against this mechanism.…”
Section: C1 Initial Branching Ratio Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations of the cycling data of Reitz et al 25 suggested that the majority of hydroxy alkoxy radicals underwent thermal decomposition, in contrast to the conclusion from the theoretical study. 36 The conclusions of the early cycling experiment suffered from an overly simplified chemical mechanism that did not include important termination reactions, notably the reaction of the isoprene-OH adduct with NO. Termination at high NO concentrations was interpreted by the authors as arising from the competition between alkoxy radical decomposition and reaction with NO.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Theoretical calculations employing quantum chemical methods and kinetic rate theories have predicted the reaction rate constants and isomeric branch ratios of the OH-isoprene reaction and several intermediate steps. [16][17][18][19][20][21][22][23][24][25] The peroxy radical kinetics, especially the 'self 'reactions between the peroxy radicals, were experimentally studied by Jenkin et al [26] The work by Zhang et al investigated the detailed mechanism of isoprene ozonolysis employing theoretical calculations. [27,28] Recent studies investigated the NO 3 -isoprene reaction by combining experimental and theoretical studies.…”
Section: Introductionmentioning
confidence: 99%